MODEL PELAKSANAAN PENDIDIKAN PESANTREN MODERN DI INDONESIA - Hidayatussaliki, Hidayatussaliki; Marno, Marno; Haris, Abd (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
According to records from the Ministry of Religious Affairs in 1997, the number of Islamic boarding schools in Indonesia has reached 9,388 (up 224%). Meanwhile, the number of students has reached 1,770,768 people (up 261%). The latest data, in 2011, the number of Islamic boarding schools is now 27,218 with as many as 3,650,000 students. Pesantren, when viewed from historical, sociological and anthropological views, this institution should be seen as an alternative educational institution in Indonesia. But the government seems to look underestimated with other formal educational institutions. On the one hand, the government recognizes the products or quality of pesantren graduates, but on the other hand, pesantren remain pesantren that are not fully recognized as educational institutions. Departing from the above reality, in turn it has invited the attention of many people to continuously observe, research, or study the dynamics, development, and existence of pesantren in Indonesia. Therefore, in this paper the author tries to present the theme of the implementation of pesantren by displaying the implementation model of modern Islamic boarding schools in Indonesia